Musik und Demenz – Perspektiven einer wachsenden Beziehung - Spintge, Ralph (DMW - Deutsche Medizinische Wochenschrift, 2019)
Dementia as a multi-facetted ailment demands multimodal approaches. Music Therapy has gained sufficient evidence as therapeutic concept in many areas of traditional medicine. Standards for research, methods and quality of application are established. For people suffering from dementia music offers a variety of beneficial effects, especially enhancing communication and quality of life. Care givers appreciate relief in emotionally aversive situations as well.
Keywords: Musik; Demenz; Morbus Alzheimer; Musiktherapie; Musik Medizin